Ultrathin silver-polysiloxane-coated plates for treatment of infected femur non-union (Transactions on Additive Manufacturing Meets Medicine, 2024)
The prevalence of fracture-related infections (FRI) poses a significant challenge in healthcare, with patients experiencing poor outcomes and lower quality of life compared to non-FRI patients. The antimicrobial coating HyProtect was applied on  plates for the treatment of infected femur non-unions. The study was conducted at the Department of Septic Trauma and Orthopaedic Surgery at BG Klinikum Hamburg, Hamburg, Germany. The study aimed to address the need for infection prevention systems by applying antibacterial coatings to orthopedic implants.The silver-polysiloxane coating is a unique method combining Physical Vapor Deposition (PVD) and Chemical Vapor Deposition (CVD) techniques to embed silver aggregates in a plasma polymer matrix. The coating demonstrated antimicrobial efficacy, no cytotoxicity, and prevention of biofilm growth in in vitro and in vivo studies. The results of the prospective non-interventional case series involving 8 patients with infected femur non-unions treated with the silver-coated implants showed positive healing outcomes with no reinfections and improved quality of life scores. The systemic silver levels remained low at 0.014 ppm in blood, indicating good biocompatibility.Conclusion: The results suggest that the silver-coated implant technology could significantly improve patient outcomes and safety during FRI surgeries. The coating process was found to be suitable for various substrates, including additive manufactured 3D printed implants.
Keywords: antimicrobial; coating; study; ultra-thing; pvd; cvd; silver